2011
DOI: 10.1007/s00424-011-1058-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of potassium channels in the inner membrane of mitochondria

Abstract: The inner membrane of the ATP-producing organelles of endosymbiotic origin, mitochondria, has long been considered to be poorly permeable to cations and anions, since the strict control of inner mitochondrial membrane permeability is crucial for efficient ATP synthesis. Over the past 30 years, however, it has become clear that various ion channels--along with antiporters and uniporters--are present in the mitochondrial inner membrane, although at rather low abundance. These channels are important for energy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 202 publications
(207 reference statements)
0
52
0
Order By: Relevance
“…Thus the endothelial mitoBK Ca channel may function as a possible signaling link between intramitochondrial calcium levels and mitochondrial ⌬⌿ and ROS. It has been previously observed that potassium channels affect mitochondrial matrix swelling, regulate the concentration of ROS, and change the mitochondrial ⌬⌿ and the transport of Ca 2ϩ into mitochondria (25,34,35). However, the physiological role of the mitoBK Ca channel in endothelial mitochondria, which is described for the first time in the present work and seems to significantly modulate mitochondrial metabolism, awaits exploration.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Thus the endothelial mitoBK Ca channel may function as a possible signaling link between intramitochondrial calcium levels and mitochondrial ⌬⌿ and ROS. It has been previously observed that potassium channels affect mitochondrial matrix swelling, regulate the concentration of ROS, and change the mitochondrial ⌬⌿ and the transport of Ca 2ϩ into mitochondria (25,34,35). However, the physiological role of the mitoBK Ca channel in endothelial mitochondria, which is described for the first time in the present work and seems to significantly modulate mitochondrial metabolism, awaits exploration.…”
mentioning
confidence: 64%
“…Potassium-selective ion channels that are similar to plasma membrane channels are found in the inner mitochondrial membrane (25,34,35): mitochondrial ATP-regulated potassium channels (mitoK ATP channels), mitochondrial BK Ca channels (mitoBK Ca channels), voltage-dependent potassium Kv1.3 channels, and not yet functionally characterized twin-pore domain weakly inward rectifying K ϩ channel (TWIK)-related acid-sensitive K ϩ (TASK) subtype-3 channel. Potassium ions control mitochondrial metabolism, primarily via the regulation of matrix volume but also through the mitochondrial membrane potential (⌬⌿), respiration, and calcium transport (18).…”
mentioning
confidence: 99%
“…The mechanism of EGb761 induced increase in the permeability of inner mitochondrial membrane to potassium ions may be also related with its action on ANT (Panov et al 1980). Moreover, constituents of EGb761 may interact with and modify some of several mitochondrial potassium channels (for review see Szabò et al 2012) and/or cation transport systems (Brierley et al 1994) present in the inner membrane.…”
Section: Discussionmentioning
confidence: 98%
“…It should be also reported that an ATP-insensitive K + import pathway has been described in potato, maize and tomato (Ruy et al 2004) and that a large-conductance Ca Koszela-Piotrowska et al 2009) and a largeconductance Ca 2+ -insensitive iberiotoxin-sensitive K + channel have been described in potato tuber mitochondria (Matkovic et al 2011). Physiology of K + channels in the inner mitochondrial membrane has recently been reviewed by Szabò et al (2012).…”
mentioning
confidence: 99%